Tumor growth and angiogenesis is impaired in CIB1 knockout mice - Zayed, Mohamed A; Yuan, Weiping; Chalothorn, Dan; Faber, James E; Parise, Leslie V (Vascular Cell, 2010)
Abstract Background Pathological angiogenesis contributes to various ocular, malignant, and inflammatory disorders, emphasizing the need to understand this process more precisely on a molecular level. Previously we found that CIB1, a 22 kDa regulatory protein, plays a critical role in endothelial cell function, angiogenic growth factor-mediated cellular functions, PAK1 activation, MMP-2 expression, and in vivo ischemia-induced angiogenesis. Since pathological angiogenesis is highly dependent on many of these same processes, we hypothesized that CIB1 may also regulate tumor-induced angiogenesis. Methods To test this hypothesis, we allografted either murine B16 melanoma or Lewis lung carcinoma cells into WT and CIB1-KO mice, and monitored tumor growth, morphology, histology, and intra-tumoral microvessel density. Results Allografted melanoma tumors that developed in CIB1-KO mice were smaller in volume, had a distinct necrotic appearance, and had significantly less intra-tumoral microvessel density. Similarly, allografted Lewis lung carcinoma tumors in CIB1-KO mice were smaller in volume and mass, and appeared to have decreased perfusion. Intra-tumoral hemorrhage, necrosis, and perivascular fibrosis were also increased in tumors that developed in CIB1-KO mice. Conclusions These findings suggest that, in addition to its other functions, CIB1 plays a critical role in facilitating tumor growth and tumor-induced angiogenesis.